Characterizing plasma and cerebrospinal fluid biomarkers relevant to neurodegeneration in captive olive baboons (Papio anubis) - Sarah J. Neal; Sriram Chitta; Elizabeth R. Magden; Joe H. Simmons (PLoS ONE, 2025)
Alzheimer’s disease and related dementias (ADRD) present a significant global disease burden that is only expected to grow in the future. As such, there is a need to develop and investigate biomarkers that identify individuals at risk of developing ADRD with the goal of providing early interventions and treatments. Non-human primate (NHP) models of neurodegeneration present opportunities to examine such biomarkers in a preclinical model with the ability to control several confounding factors present in research with humans. Baboons naturally develop several ADRD-related neuropathologies that humans also exhibit, including age-related tau and amyloid deposition. However, to our knowledge, there are no data characterizing fluid biomarkers relevant to neurodegeneration or ADRD in baboons. We collected plasma (N = 139) and cerebrospinal fluid (CSF, N = 44) from captive baboons ranging in age from 3–19 years old. We characterized biomarkers as a function of age, sex, and rearing status in baboons using a bead-based bioplex human assay (Thermo Fisher Scientific’s Neuroscience 18-Plex Human ProcartaPlex™ Panel). Fluid biomarkers were more detectable in CSF compared to plasma. Additionally, while sex and rearing did not significantly predict biomarkers in baboons, age significantly predicted levels of eight of the 12 biomarkers detected in the assay. Linear regressions showed that CSF levels of total tau, pTau181, NGF-beta, GFAP, NF-H, and S100B were higher in older baboons, as were plasma levels of NGF-beta. Lastly, older baboons showed a higher incidence of co-occurrence of multiple biomarkers as measured in CSF, but not in plasma. These data show that baboons exhibit age-dependent changes in biomarkers used in humans for clinical screening, diagnosis, and prognosis of ADRD, thereby further demonstrating the value of baboons as a model of aging and, possibly, ADRD.